YOU and YOUR CREDIT: Further Resources - Michael S. Gutter; Joan P. Elmore; Travis P. Mountain (EDIS)
This document is FCS7235, part of the YOU and YOUR CREDIT series by Michael S. Gutter, Joan P. Elmore, and Travis P. Mountain. Published by the UF Department of Family Youth and Community Sciences, September 2008.